Biological testing of stomatological phytomedicines - Matsiuk , Oksana; Kaliuzhnaia, Olga; Vyshnevska , Liliya (Annals of Mechnikov’s Institute, 2022)
Introduction. Taking into account the lack of complex stomatological phytomedicines on the domestic pharmaceutical market, the composition and technology of compositions with a combination of several types of medicinal plant raw materials were developed, which creates prerequisites for expanding and strengthening the desired therapeutic effect. On the basis of theoretical reasoning and experimental studies, we developed an emulsion ointment for the treatment of angulitis and a mouth rinse for use in halitosis. During the pharmaceutical development of dental phytoremedies, one of the directions of our experimental research was conducting biological tests, in particular the analysis of microbiological purity and the determination of harmlessness. The purpose of the work was to study the microbiological purity and determine the harmlessness of the developed stomatological phytomedicines for the treatment of angulitis and halitosis. Materials and methods. In the tests, experimental samples of the developed phytomedicines were used - emulsion ointment for the treatment of angulitis and mouth rinse for use in halitosis. Testing of microbiological purity of non-sterile medicinal products was carried out according to the methods given in the general articles of SPU 2.0. In accordance with the requirements of the SPU, the sterility of the nutrient media, the solvent, the growth properties of the nutrient media, and the suitability of the method for determining the total number of viable cells were checked. Biotesting was carried out on the biological model monoculture of Paramecium caudatum. Infusoria were grown in the Lozyn-Lozynsky nutrient medium at a temperature of 22±2 °С, using yeast suspension for nutrition. To control the toxicity of the drug, the effect of the test samples on the physiological functions of the culture was evaluated: change in motility, death of the organism and the rate of reproduction. Results and discussion. The results of testing the growth properties of the nutrient media showed that they met the growth properties and passed the sterility test in accordance with the requirements of SPU 2.0, and the test microorganisms met the taxonomic characteristics - the morphology of the colonies on the media and the morphology of the cells under microscopy were typical for the corresponding strain. The results of testing the suitability of the method for determining the total number of viable microorganisms showed that the method of surface seeding on 1 ml cups with a 1:10 dilution of test samples with an inactivator is suitable for determining the number of microorganisms in 1 ml of the drug and can be used during testing. The microbiological purity test of stomatological phytomedicines showed that for each sample Total aerobic microbial count was no more than 102 CFU/g, the Total yeast and mold count was no more than 10 CFU/g, P. aeruginosa and S. aureus weren’t detected in 1 g, which meets the requirements of the SPU. Control of the toxicity of experimental samples of stomatological phytomedicines by means of biotesting showed that the experimental samples are non-toxic. Conclusions. The results of the study of samples of stomatological phytomedicines - emulsion ointment for the treatment of angulitis and mouth rinse for use in halitosis, which were stored at a temperature of 25 ± 2 for 27 months, according to the "microbiological purity" indicator, show that for each sample TAMC does not exceed 102 CFU/g, TYMC does not exceed 10 CFU/g, P. aeruginosa and S. aureus weren’t detected in 1 g, which meets the requirements of the DFU. Toxicity control of samples of developed stomatological phytomedicines by means of biotesting on P. caudatum cells showed high values of the observed test parameters - high motor activity of cells and the rate of their reproduction, which indicates the non-toxicity of phytoremedies.